Conditions for Success in a Community Based Conservation Initiative: An Analysis of Triggering Moments and Catalytic Elements in Nuha - Nurhady Sirimorok; Eko Rusdianto (Forestry Faculty, Universitas Hasanuddin, 2020)
What accounts for a successful community-based conservation (CBC) initiative? A bulk of studies has answered the question by identifying the principles as well as underlying relations that make up successful cases. However, rarely do they extend to examine the basic elements (or ingredients) that contribute to a successful case. Using the analytic framing of triggering moments and catalytic elements, this study describes the key factors that contributed to ongoing successes in achieving the outputs and goals of CBC. A recent CBC project in the Lake Malili Complex of South Sulawesi is examined as a case study to test the framework. The CBC initiative was carried out by a local NGO and university. The case village (Nuha) is chosen for its ability to continue implementing programmatic objectives according to project reports. In-depth interviews, a close review of grey literature about the project, as well as field observations in Nuha and surrounding villages provide the data that forms the basis of the analysis about the factors contributing to Nuha success. Findings show that the framework of triggering moments and catalytic elements can help to show the key factors of crises and windows of opportunity that contribute strongly to stimulating community responses to a CBC initiative. Furthermore, although not all catalytic elements were present, certain identified factors – participation, commitment of key actors, funding, capacity building, partnership with supportive organizations and governments, and leadership – were strong enough to stimulate effective implementation of the CBC initiative. Nevertheless, the analytic framework of triggering moments and catalytic elements is less capable of provide the context for why the catalytic elements were present prior to the introduction of the CBC initiative.